Earth science - Tarbuck, Edward J.; Lutgens, Frederick K. (Boston : Pearson, 2015)
"Earth science, 14th edition, is a college-level text designed for an introductory course in Earth science. It consists of seven units that emphasize broad and up-to-date coverage of basic topics and principles in geology, oceanography, meteorology, and astronomy. The book is intended to be a meaningful, nontechnical survey for undergraduate students with little background in science. Usually these students are taking an Earth science class to meet a portion of their college or university's general requirements. In addition to being informative and up-to-date, Earth science, 14th edition, strives to meet the need of beginning students for a readable and user-friendly text and a highly usable "tool" for learning basic Earth science principles and concepts"--Provided by publisher.
Includes index.
Keywords: Earth sciences -- Textbooks